Institutional settings in a rice cluster: Assessing the effects of social capital on learning in Malaysia - Ng, B.K.; Magli, A.S.; Wong, C.Y.; Govinda, V.C. (2014)
Based on a case study of the Sekinchan rice cluster in Malaysia, this paper provides empirical evidence demonstrating that geographic proximity goes hand-in-hand with social capital. The paper argues that the study of social capital within a geographic dimension (such as Regional Innovation Systems and clusters) needs to take place in its institutional context. Thus, agricultural cluster development policies must address the 'soft' elements of the cluster in fostering cooperative relationships and "social contracts" among the cluster actors. Findings also indicate that the cluster's learning processes take place mainly in the form of informal learning and learning by doing, in which the effects of social cohesiveness, trust and connectedness are particularly important. The sustainability issues encountered by the rice cluster and key policy implications conclude the paper.